Research on fuzzy comprehensive evaluation of fire risk in ancient buildings - Zhiming Wang; Jiangnan Peng; Xinzhi Liu; Changan Di; Zhifang Zhang; Yining Wang (Emergency Management Science and Technology)
The study of the distribution pattern of fire risk in ancient buildings can provide a starting point for emergency measures to be taken in case of possible fires. Based on the fire characteristics, system complexity, and geographic information attributes of large palace ancient building complexes, this paper adopts a fuzzy comprehensive evaluation method combining fuzzy mathematics and analytic hierarchy process to construct a fire risk evaluation system for ancient buildings, which includes six criteria and 28 indicators such as the value index, and the fire likelihood. For the evaluation method of this system, the expert scoring and Analytic Hierarchy Process are used to determine the weights of various indicators. Then, the multiple rounds of expert analysis with a review of relative literature, the membership degree of each indicator is analyzed one-by-one, and the final risk model, and risk factor are determined. By combining MHMapGIS technology, this comprehensive evaluation method was applied as an example to the Imperial Palace (large Ming and Qing ancient architectural buildings) in Beijing (China) for grid and visual analysis, and the rationality of the results were verified. The evaluation results can intuitively and reasonably show the distribution of fire risk, indicating that the constructed evaluation system and its model method display a certain of feasibility.